Intra-articular Steroid Injection for the Treatment of Idiopathic AdhesiveCapsulitis of the Shoulder (The Planet, 2024)
Introduction: Adhesive capsulitis, commonly known as frozen shoulder, is a painful and debilitating condition characterized by inflammation and stiffening of the shoulder joint, leading to a restricted range of motion. Treatment options for adhesive capsulitis vary, but intra-articular corticosteroid injections have been widely used. This study aimed to assess intra-articular steroid injection for the treatment of idiopathic adhesive capsulitis of the shoulder. Methods & Materials: This retrospective study, conducted between January and August 2024 at Monno Medical College Hospital, included 566 patients with idiopathic adhesive capsulitis treated with intra-articular corticosteroid injections. All analyses were conducted using SPSS version 26.0. Result: This study evaluated the effectiveness of intra-articular corticosteroid injections for treating idiopathic adhesive capsulitis in 566 patients. In this study 69.3% of patients achieved complete pain relief, while 26.1% experienced maximal pain reduction. The majority of patients (50.2%) experienced pain relief within 7-10 days, with 45.2% reporting relief within 11-15 days. The follow-up compliance rate was high, with 95.4% of patients attending all follow-up visits. A small subset of patients (1.2%) required surgical referral due to persistent symptoms, and complications such as post-injection pain flare (1.9%) and transient hyperglycemia (1.6%) were rare but noted. Conclusion: In conclusion, intra-articular corticosteroid injections are an effective and safe treatment option for patients with idiopathic adhesive capsulitis, providing significant pain relief and improving range of motion in the majority of patients. The low complication rate and rapid onset of action make it a favorable non-surgical treatment.
Keywords: Intra-articular Steroid Injections; Adhesive capsulitis; Frozen shoulder; Physical activeity